How Does Servant Leadership Influences Creativity? Enhancing Employee Creativity via Creative Process Engagement and Knowledge Sharing - Chen, Meizhao; Zada, Muhammad; Khan, Jawad; Saba, Noor Ul (Frontiers in Psychology, 2022)
Grounding on social exchange theory and using the creative process engagement as a lens, this article study investigates the influence of servant leadership on employee creativity. In addition, the research examines the role of knowledge sharing in the link between servant leadership and employee creativity. Time lag method was used to collect the data from 242 employees and 57 managers employed in Chinese publicly listed companies. The data collection was divided into two parts. The subordinates were asked to rate servant leadership, their creative process engagement behavior, and knowledge sharing. The supervisors were asked to rate their associates regarding employee creativity. According to the results, employees' creative process engagement behaviors mediated servant leadership and employees' creativity. In addition, the link between servant leadership and employees' creativity was strengthened by knowledge sharing. A detailed model is also provided, highlighting the significance of leadership, work engagement, and knowledge sharing in fostering employee creativity in the Asian environment